Factors Related to the Utilization of Chronic Disease Management Programs in Patients with Type 2 Diabetes Mellitus - Evi Gustika; Endang Budiati; Dewi Rahayu; Atikah Adyas; Dian Utama Pratiwi Putri (Knowledge Dynamics, 2025)
Background: The Chronic Disease Management Program is an integrated proactive health service involving patients, health facilities, and BPJS Kesehatan to improve care for individuals with chronic diseases, including type 2 diabetes mellitus (T2DM). This study aimed to analyze factors influencing the utilization of Prolanis among T2DM patients in West Pesisir Regency. Methods: This quantitative study employed a cross-sectional design with 149 respondents selected through stratified random sampling. Data were collected between February and March 2025 and analyzed using Chi-square tests and multivariate logistic regression. Results: Family support (p = 0.000), illness perception (p = 0.000), perceived needs (p = 0.014), cross-sector support (p = 0.017), and health facility availability (p = 0.004) were significantly associated with Prolanis utilization. Among these, family support was the most dominant factor (OR = 10.26), indicating that patients with low family support were over 10 times more likely to show low program utilization compared to those with strong family support. Conclusion: Family support is the key determinant of Prolanis utilization among T2DM patients. Strengthening family involvement may enhance participation in chronic disease management programs.